Genetics of Legg-Calvé-Perthes Disease: A Review Study - Mohammad Reza Sobhan; Nasim Namiranian; Samira Asadollahi; Hossein Neamatzadeh (Mazandaran University of Medical Sciences, 2021)
Background: Legg-Calvé-Perthes Disease (LCPD), a juvenile hip disorder, is caused by impaired blood flow to the femoral head. In severe LCPD cases, the femoral head may develop a flattening deformity. Furthermore, if LCPD is diagnosed at the later stages, it causes early osteoarthritis of the hip. The etiology of LCPD is complex and embraces both genetic and epigenetic factors. Objectives: This review attempts to summarize the current knowledge on the role of these genetic variants in the incidence of LCPD. Methods: We searched for articles published in English using the special related search terms. Results: The genetic causes of this disease include mutations in the genes of thrombophilia factors, such as FV Leiden and anticardiolipin antibodies. The mutations of COL2A1, TRPS1, eNOS genes are the other causes. Moreover, the clinical symptoms of avascular necrosis may be indiscernible in patients with Gaucher's disease or LCPD, and the differential diagnosis is a challenge. Conclusions: The results indicated that genetic testing may be useful in diagnosing and managing patients with juvenile hip disorders.